1985
DOI: 10.1152/ajpgi.1985.248.1.g46
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of zinc absorption by luminally and vascularly perfused rat intestine

Abstract: Zinc absorption by intestines of rats fed either zinc-deficient or zinc-adequate diets was measured by simultaneous luminal and vascular perfusion. The rate of absorption increased steadily for the first 30-40 min of perfusion over the entire lumen zinc concentration range examined (8-234 microM). During the last 10 min of perfusion the absorption rate did not change appreciably with time (steady state), and absorption by intestines from the zinc-depleted rats showed evidence of both carrier-mediated (saturabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 0 publications
0
51
0
Order By: Relevance
“…As a highly charged, hydrophilic ion, Zn(II) cannot cross biological membranes by simple diffusion, and specialized mechanisms therefore must exist for its cellular uptake and release. Zinc absorption has been studied extensively in several model systems, particularly perfused intestinal segments (2,3) and isolated intestinal cells (4). Zinc transport has been characterized in many cell types, including fibroblasts (5), hepatocytes (6,7), placental trophoblasts (8), and endothelial cells (9).…”
mentioning
confidence: 99%
“…As a highly charged, hydrophilic ion, Zn(II) cannot cross biological membranes by simple diffusion, and specialized mechanisms therefore must exist for its cellular uptake and release. Zinc absorption has been studied extensively in several model systems, particularly perfused intestinal segments (2,3) and isolated intestinal cells (4). Zinc transport has been characterized in many cell types, including fibroblasts (5), hepatocytes (6,7), placental trophoblasts (8), and endothelial cells (9).…”
mentioning
confidence: 99%
“…However, detailed information on the intestinal absorption of zinc is likely insufficient at present. Functional studies on the intestinal absorption of zinc using preparations such as everted rat gut sacs, 15,16) the isolated vascularly perfused rat intestine, [17][18][19][20] and intestinal brush-border membrane vesicles from the small intestine of rats 21) provide evidence of saturable components of zinc transport. In most experiments, zinc absorption was measured indirectly.…”
Section: In Vitro Study On the Transport Of Zinc Across Intestinal Epmentioning
confidence: 99%
“…Experiments with radioisotopes and stable isotopes have identified, through kinetic analysis and metabolic modeling, major pathways by which dietary zinc is processed and how organs in concert produce a fairly effective homeostatic control over absorption and excretion (44,84). Evidence shows reduction in dietary zinc content produces a marked increase in intestinal absorption and decrease in intestinal zinc losses, with urinary losses that are low and refractory to zinc intake (2,32,35,53,63,74,97,98,107). The current dietary recommendations for humans have been based on calculations where zinc intake must balance losses (84).…”
Section: Introductionmentioning
confidence: 99%
“…At the organ and cellular levels, kinetic studies have shown zinc uptake kinetics exhibit mediated and nonmediated components (74,85,87,89,97). Mediated uptake suggests a saturable mechanism and involvement of a transporter(s).…”
Section: Introductionmentioning
confidence: 99%